Respuesta :

Answer:

answer is A

Step-by-step explanation:

(3[tex]x^{2}[/tex]+5x+1) ([tex]x^{2}[/tex]−2x+4)

=(3[tex]x^{2}[/tex]+5x+1)([tex]x^{2}[/tex]+−2x+4)

=(3[tex]x^{2}[/tex])([tex]x^{2}[/tex])+(3[tex]x^{2}[/tex])(−2x)+(3[tex]x^{2}[/tex])(4)+(5x)([tex]x^{2}[/tex])+(5x)(−2x)+(5x)(4)+(1)([tex]x^{2}[/tex])+(1)(−2x)+(1)(4)

=3[tex]x^{4}[/tex]−6[tex]x^{3}[/tex]+12[tex]x^{2}[/tex]+5[tex]x^{3}[/tex]−10[tex]x^{2}[/tex]+20x+[tex]x^{2}[/tex]−2x+4

=3[tex]x^{4}[/tex][tex]x^{3}[/tex] + 3[tex]x^{2}[/tex] + 18x +4